-6=y+3

Simple and best practice solution for -6=y+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=y+3 equation:


Simplifying
-6 = y + 3

Reorder the terms:
-6 = 3 + y

Solving
-6 = 3 + y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1y' to each side of the equation.
-6 + -1y = 3 + y + -1y

Combine like terms: y + -1y = 0
-6 + -1y = 3 + 0
-6 + -1y = 3

Add '6' to each side of the equation.
-6 + 6 + -1y = 3 + 6

Combine like terms: -6 + 6 = 0
0 + -1y = 3 + 6
-1y = 3 + 6

Combine like terms: 3 + 6 = 9
-1y = 9

Divide each side by '-1'.
y = -9

Simplifying
y = -9

See similar equations:

| 10+4x=-14+6x | | 15b^2+10b-8=0 | | .75x+8=f(x) | | u-5=-8 | | sin(4x)=1 | | 5=-21+3t | | 6+w=-2 | | (7x+4)(3x+9)= | | y=226-33x | | -36+6x=12 | | 3.6x+8=26 | | n-10=-27 | | 1.25g+4=13.5 | | a^2-x=0 | | 12-4h=6 | | j-(-17)=30 | | 5-3*x=20 | | t+13.4=-4.5 | | 1p-5=8 | | 4(p+5)=7 | | 36t^2=9 | | -6n+5n=-3 | | 4(p+-5)=7 | | (6x-6)(4x+9)=0 | | -6r+5s+2t=-11 | | 3(x)=8.25 | | 3x^2-6x+4y^2-13=0 | | 12(y+2)=36 | | 8(x)=8.25 | | 8x+7=127 | | 170+0.25x=375 | | 7200=(756)R(2.5) |

Equations solver categories